The pleural mesothelium in development and disease - Batra, Hitesh; Antony, Veena B. (Frontiers in Physiology, 2014)
The pleural mesothelium, derived from the embryonic mesoderm, is formed by a metabolically active monolayer of cells that blanket the chest wall and lungs on the parietal and visceral surfaces, respectively. The pleura and lungs are formed as a result of an intricate relationship between the mesoderm and the endoderm during development. Pleural Mesothelial Cells (PMCs) are known to express Wilms tumor-1 (Wt1) gene and in lineage labeling studies of the developing embryo, PMCs were found to track into the lung parenchyma and undergo mesothelial-mesenchymal transition (MMT) to form α-smooth muscle actin (α-SMA)-positive cells of the mesenchyme and vasculature. There is definite evidence that mesothelial cells can differentiate and this seems to play an important role in pleural and parenchymal pathologies. Mesothelial cells can differentiate into adipocytes, chondrocytes and osteoblasts; and have been shown to clonally generate fibroblasts and smooth muscle cells in murine models. This supports the possibility that they may also modulate lung injury-repair by re-activation of developmental programs in the adult reflecting an altered recapitulation of development, with implications for regenerative biology of the lung.